“THE BEING OUTSIDE OF BEING, WITHIN BEING”. THE QUESTION OF HUMAN CONSCIOUSNESS IN NOVALIS’ “FICHTE-STUDIEN” (Revista Kriterion, 2020)
The question of human consciousness is a crucial part of Novalis’ aim of construing a self-critique of the I, or critique of human identity, as it is proposed in his “Fichte-Studien” (1795-1796). Namely, this question is an intermediary stage in said critique, serving as proof for Novalis’ theory of the opposites, the fundamental stage, and his position on philosophizing, the final stage of this endeavor, which will be at the basis of his whole philosophical system; and as such, it is a topic of great importance, as it is not only a link in a chain of thought which aims at proving the organicity or living heterogeneity – and not Fichte’s machine-like homogeneity – of the human but is also a key topic towards the resolution of Novalis’ problem of philosophy as an existential problem. Given this, the present article intends to situate the question of human consciousness in the framework of Novalis’ greater scope of a critique of the I; and from then, to comment on Novalis’ own position on the problem of human consciousness, as it is stated in the formula “Consciousness is the Being outside of Being, within Being”; a position which further separates the young poet from Fichte, as it renders him closer and closer to other young idealists, such as Hölderlin or Schelling.